Hyponatremia in cancer patients: Time for a new approach. (June 2016) - Berardi, Rossana; Rinaldi, Silvia; Caramanti, Miriam; Grohè, Christian; Santoni, Matteo; Morgese, Francesca; Torniai, Mariangela; Savini, Agnese; Fiordoliva, Ilaria; Cascinu, Stefano
Highlights: Hyponatremia is relevant in cancer patients because it may have a negative impact on outcome, on quality of life and on length of hospitalization. There are evidences that the inappropriate antidiuretic hormone syndrome (SIADH) is the most common cause of hyponatremia in cancer patients. An early detection, monitoring and prompt management is needed to improve the patient's outcome and several options are available. Several studies have demonstrated the efficacy and good tolerability of Tolvaptan for the treatment of SIADH-related hyponatremia even in cancer patients. Abstract: Hyponatremia is a common electrolyte disorder in cancer patients. It may be related to cancer, to anti-cancer therapy or to other concomitant treatments. In this setting hyponatremia is often caused by the syndrome of inappropriate anti-diuretic hormone secretion, which is due to the ectopic production of antidiuretic hormone (vasopressin), to extracellular fluid depletion, to renal toxicity caused by chemotherapy or to other underlying conditions. Recent studies suggested that hyponatremia might be considered a negative prognostic factor for cancer patients therefore its early detection, monitoring and management might improve the patient's outcome. Treatment of hyponatremia depends on patient's symptoms severity, onset timing and extracellular volume status. In this review we summarize the main causes of hyponatremia in cancer patients and its management, including the available treatment options.